Przyszłość państwa dobrobytu - dostosowanie czy nowy paradygmat? - Kowalski, Ryszard (The Future of the Welfare State - Adjustment or a New Paradigm?, 2009)
The future of the welfare state is determined by social and economic processes which accompany (or continue) the shift from the industrial to post-industrial society including employment structural changes in highly developed countries, the aging of societies, the emerging of a new family model, and the maturation of social schemes implemented by the welfare state. These processes lead to new social risks which will not result in creating the welfare state based on a new paradigm but merely corrections of its original form, The first reason is the existence of institutional resistance to such changes, and the second one - the existing social democratic model of the welfare state is likely to be a response to the new risks. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 164-171